STATUS OF PEATLAND FIRE RESEARCH IN INDONESIA - Lailan Syaufina (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Peatland fire research has been on the increasing trend since 1997/1998 when fire episode experienced by Indonesia and ASEAN region. Its impact on transboundary haze pollution has not merely related to environmental but on social and political issues. Since then, research on peatland fire has been on local and global concerns. International scientific journals on peatland fire in the period of 1997-2014 were reviewed and analysed descriptively. The study shows that in the earlier stage, researches covered peatland fire characteristics, fire behaviour, fire causes and fire impacts on peat and biodiversity in limited area. Research concerns had been broadened to ecological, economical, social aspects, and even political aspects. Greater impacts on transboundary haze pollution had attracted scientists to study on haze-air pollution relationship with special concern on health and economical aspects. Moreover, peatland fire and climate change issues including greenhouse gas (GHG) emission had been covered and become an iconic topic of peatland fire studies. Geographycally, almost all peatland fire studies focused in Sumatera and Kalimantan. In the last two decades period, peatland fire researches had been explored and developed to spatial analyses on fire prone areas mapping, modelling on fire occurence prediction, haze trajectory, hotspot accuracy as fire indicator, and the latest issue was burned area estimation in relation to predict GHG emission. Key words: peatland fire, transboundary haze, hotspot, climate change, emission